The Mediating Role of Profitability in the Green Accounting-Firm Value Relationship: Evidence from Indonesian Primary Sectors - Saragih, Afni Eliana; Ratnawati (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
Environmental and social impact disclosure pressures from investors and stakeholders have accelerated the adoption of environmental accounting and reporting systems, commonly referred to green accounting. Green accounting reflects a company's accountability toward the environmental impact of its operational activities, thereby enhancing stakeholder trust and positively influencing firm value. This study aims to examine the influence of green accounting implementation on firm value and to test the mediating role of profitability in this relationship. Employing purposive sampling methods, the sample is drawn from companies across seven major sectors listed on the Indonesia Stock Exchange over the 2022-2024 period. The research methodology adopts a path analysis framework using multiple linear regression. The empirical results demonstrate that green accounting implementation does not significantly influence firm value. Additionally, profitability does not significantly mediate the relationship between green accounting and firm value. These findings suggest that green accounting practices have not been effectively integrated into corporate value creation. These findings suggest that companies and regulators need to strengthen the mandatory disclosure framework for green accounting practices